MEKANISME DAN PENGELOLAAN WAKAF UANG PADA IBU-IBU PENGAJIAN MASJID AL MUCHTAR GOTONG ROYONG III SAKO PALEMBANG - Saprida, Saprida; Umari, Zuul Fitriani (LPPM Universitas Bina Bangsa, 2024)
This community service outreach activity discusses the mechanisms and management of cash waqf. This socialization was carried out because of the increasing distribution of cash waqf among the community and the many questions from the Al Muchtar Mutual Cooperation III Mosque recitation women regarding cash waqf procedures made the author interested in studying and holding outreach regarding cash waqf procedures. The aim of this socialization activity is to provide an understanding of cash waqf to recitation mothers with the hope that socialization participants can understand in detail about cash waqf. The methods used in this service are lecture, discussion and question and answer methods. The results of this service show that cash waqf management in Indonesia is grouped into two, namely cash waqf managed by sharia banks and private institutions. In practicing cash waqf, there are at least three things that must be considered. First, the method of collecting funds (fundraising), Second, managing the funds that have been successfully collected. Third, distribution of the results that can be created to the beneficiaries. Waqf money is jawaz (permissible) and is only allowed to be distributed to things that do not conflict with sharia. The principal value of waqf assets in the form of money must be guaranteed to be preserved, and cannot be sold, given away, and/or inherited